2018
DOI: 10.17816/ov11125-33
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and etiological characteristic, classification and treatment of aseptic corneal ulcers

Abstract: Introduction. Aseptic corneal ulcers are among rare, but severe, torpid diseases. The aim is to study the etiology, develop a clinical classification of the corneal aseptic ulcer, and determine the tactics of their treatment. Material and methods. A total of 40 patients (47 eyes) were examined when admitted as emergency with an aseptic ulcer of the cornea. In addition to traditional examination methods, the optical coherence tomography was performed, ulcer area and depth were recorded, and the collagenolytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Trauma was most common causative factor 486(81%) this finding is supported by the work of Musch DC, Sugar A, Meyer RF et al and Titiyal JS, Negi S, Anand A, Tandon R, Sharma N, Vajpayee RB et al [16,17] . Most of the ulcer were 3 mm to 6 mm in size and Paracentral in location, this finding is similsr to the study of Mascarenhas J, Srinivasan M, Chen M, Rajaraman R, Ravindran M et al, Khare P, Shrivastava M, Kumar K et al and Brzheskaya I.V., Somov E.E [13,18,19] . Corneal ulcer associated with hypopyon in 22(12.5%) patients.…”
Section: Discussionsupporting
confidence: 83%
“…Trauma was most common causative factor 486(81%) this finding is supported by the work of Musch DC, Sugar A, Meyer RF et al and Titiyal JS, Negi S, Anand A, Tandon R, Sharma N, Vajpayee RB et al [16,17] . Most of the ulcer were 3 mm to 6 mm in size and Paracentral in location, this finding is similsr to the study of Mascarenhas J, Srinivasan M, Chen M, Rajaraman R, Ravindran M et al, Khare P, Shrivastava M, Kumar K et al and Brzheskaya I.V., Somov E.E [13,18,19] . Corneal ulcer associated with hypopyon in 22(12.5%) patients.…”
Section: Discussionsupporting
confidence: 83%
“…According to WHO, blindness secondary to corneal disorders is one of the leading causes of loss of sight [ 12 ]. Each year, 1.5–2.0 million cases of monocular blindness secondary to various corneal lesions are documented worldwide [ 13 , 14 ]. The most frequent causes of corneal lesions include keratitis and corneal ulcers [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning corneal ulcers in particular, the available clinical experience showed that they are a group of rare but very serious conditions, which are difficult to manage. For example, according to a number of authors, anatomical destruction of the eye is the ultimate outcome in 8-9% of the cases, and in 17% of the cases, enucleation is undertaken due to lack of treatment effect [ 13 ]. Corneal damage leading to corneal ulceration occurs as a combination of direct microbial invasion and a release of collagenases, secondary to host chemotaxis of leukocytes [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local disorders include herpetic keratitis and paralytic lagophthalmos) leading to severe trophic impairments in the cornea. 9 The most common location for ulcers is the central cornea with >6 mm in size.…”
Section: Clinical Features Of Corneal Ulcer Patientsmentioning
confidence: 99%